2021
DOI: 10.1186/s40703-020-00136-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and prediction of brittle failure in rock blocks having a circular tunnel under uniaxial compression using acoustic Emission technique: laboratory testing and numerical simulation

Abstract: In this research, the failure mechanism and anomalous behavior of intact and jointed rock block having a circular tunnel under compression are studied. This was done by monitoring the progressive failure of a rock tunnel subjected to uniaxial loading. The tests were conducted in sandstone blocks and “Acoustic Emission” (AE) technique was used to identify the crack damage and other failure attributes. Three cases have been considered in the research, i.e. tunnel in the intact rock, with horizontal joints, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Kim et al [9] considered that acoustic emission technology can determine the cracking stress and damage stress of rocks. Das et al [10] conducted uniaxial compression tests on tunnel experiments, and the results showed that acoustic emission technology can analyze and predict the brittle failure of tunnels.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [9] considered that acoustic emission technology can determine the cracking stress and damage stress of rocks. Das et al [10] conducted uniaxial compression tests on tunnel experiments, and the results showed that acoustic emission technology can analyze and predict the brittle failure of tunnels.…”
Section: Introductionmentioning
confidence: 99%